1990
DOI: 10.1007/bf02412646
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration and the elderly

Abstract: Aspiration is prevalent in the elderly but its association with impairment of oral intake and gastroesophageal reflux is often misunderstood. This paper describes the causes, pathophysiology, and consequences of aspiration and their unique features in aged persons. It also explains how videofluoroscopic evaluation can assess current function while limiting factors that result in misinformation. The management of aspiration is discussed, emphasizing the importance and difficulties in maintaining functional well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
2
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 70 publications
1
69
2
3
Order By: Relevance
“…More than 270,000 veterans with dysphagia accounted for 350,000 visits and admissions to VA facilities annually [2]. One of the most common treatments for dysphagia is thickening liquids, thereby modifying swallowing physiology by altering fluid rheology [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 270,000 veterans with dysphagia accounted for 350,000 visits and admissions to VA facilities annually [2]. One of the most common treatments for dysphagia is thickening liquids, thereby modifying swallowing physiology by altering fluid rheology [3].…”
Section: Introductionmentioning
confidence: 99%
“…A survey of VA acute facilities completed by the Office of Inspector General reported that speechlanguage pathologists recommended a downgrade in diet consistency 68 percent of the time and recommended that all liquids be thickened 46 percent of the time following abnormal swallowing evaluations [6]. In certain circumstances (e.g., neurodegenerative conditions such as dementia), thickened liquids are recommended as a longterm solution for safe hydration [3]. As many as 31 percent of residents in long-term care facilities receive altered diets, with an estimated 28 percent receiving thickened liquids [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that 40% of adults aged 60 and older have dysphagia [38,39]. Stina [40] investigated the connection between swallowing functions and quality of life in patients with PD.…”
Section: Dysphagiamentioning
confidence: 99%
“…Beta agonists might contribute to gastroesophageal reflux (GER) by decreasing lower esophageal pressure (Yamaya et al, 2001). GER probably occurs more often when the patient is bedridden, and vomiting may be more frequent in patients with GER, adding to the risk of aspiration pneumonia (Feinberg et al, 1990). Aspiration pneumonia contributes to infection of the lung due to the aspiration of bacteria contained in (Barish et al, 1985) because they either aspirate smaller volumes or are able to clear bacteria rapidly.…”
Section: Elderly Patients: Dysphagia and Aspiration Pneumoniamentioning
confidence: 99%